Spectroscopic Fingerprints of Intermolecular H‐Bonding Interactions in Carbon Nitride Model Compounds. Issue 53 (27th August 2018) - Lanzilotto, Valeria; Silva, J. Luis; Zhang, Teng; Stredansky, Matuš; Grazioli, Cesare; Simonov, Konstantin; Giangrisostomi, Erika; Ovsyannikov, Ruslan; De Simone, Monica; Coreno, Marcello; Araujo, C. Moyses; Brena, Barbara; et al.
Abstract: The effect of intermolecular H‐bonding interactions on the local electronic structure of N‐containing functional groups (amino group and pyridine‐like N) that are characteristic of polymeric carbon nitride materials p‐CN(H), a new class of metal‐free organophotocatalysts, was investigated. Specifically, the melamine molecule, a building block of p‐CN(H), was characterized by X‐ray photoelectron (XPS) and near edge X‐ray absorption fine structure (NEXAFS) spectroscopy. The molecule was studied as a noninteracting system in the gas phase and in the solid state within a H‐bonded network. With the support of DFT simulations of the spectra, it was found that the H‐bonds mainly affect the N 1s level of the amino group, leaving the N 1s level of the pyridine‐like N mostly unperturbed. This is responsible for a reduction of the chemical shift between the two XPS N 1s levels relative to free melamine. Consequently, N K‐edge NEXAFS resonances involving the amino N 1s level also shift to lower photon energies. Moreover, the solid‐state absorption spectra showed significant modification/quenching of resonances related to transitions from the amino N 1s level to σ* orbitals involving the NH2 termini. Abstract : Carbon nitride models : H‐bonding interactions between the amino groups and the triazine N atoms of melamine, which are relevant to the structure of polymeric carbon nitrides, mainly modify the energy of the N 1s level of the H‐donor, leaving the chemical environment of the H‐acceptor almost unperturbed (see figure).